Malnutrition and Obesity Prevalences in Geriatric Patients: Malnutrition and Obesity Prevalences - Turkbeyler, İbrahim H; Ozturk, Zeynel A; Abiyev, Azer; Efendioglu, Eyüp M; Yildiz, Hamit (Progress in Nutrition, 2020)
Aim: All societies, including Turkish society, are experiencing a dramatic growth in proportion of elderly individuals. Geriatric malnutrition and obesity are substantial health problems. The aim of this study is to investigate the prevalence of malnutrition and obesity in elderly individuals who attended a geriatric outpatient clinic in Turkey.Methods: This study included 520 elderly patients. All patients underwent Mini Nutritional Assessment–Short Form (MNA-SF) test via face to face interview. The participants were divided into four groups, as follows: underweight group (BMI